Optimalisasi Penggunaan Benih Mandiri untuk Meminimalisir Biaya dan Ketergantungan pada Kegiatan Pembesaran Ikan Nila - Serdiati, Novalina; Nasmia, Nasmia; Antara, Made; Tahya, Akbar Marzuki; Safir, Muhammad (LPPM Universitas Trunojoyo Madura, 2023)
The village of Tulorantea is one of the villages where the community is engaged in tilapia fish farming. The tilapia fingerlings used are generally imported from other regions at a relatively high cost ( Rp. 1000/individual with a size of 3-5 cm), and they are often ordered in large quantities. This situation poses a threat to the sustainability of small-scale tilapia farming. In addition, the profits obtained by fish farmers at the end of the cultivation period are relatively low. One of the efforts to address this issue is the use of self-produced fingerlings. This can be achieved successfully if the breeding process of tilapia is well understood by the farmers. Therefore, the purpose of this community service is to provide farmers with an understanding of the proper methods for tilapia breeding to produce self-produced fingerlings and strategies for marketing quality fishery products. This activity is conducted in the form of counseling, with participants from the village government and fish farmers. Two weeks after the counseling, 100 potential breeders (25 males and 75 females) and net cages for acclimatizing the potential breeders are handed over to the fish farmers. The results of the activity show that the fish farmers are very enthusiastic about participating in the program and becoming involved in tilapia breeding to produce self-produced fingerlings to support their farming activities. In conclusion, problem-based counseling activities aimed at addressing the challenges faced by fish farmers have increased the enthusiasm of fish farmers in their efforts to achieve optimal production.